Study protocol for a multi-centre randomised controlled trial of the Thai early intervention for autism: Assistive Technology for Caregivers (TEI4A-ATC) across nine hospitals in health region 1, northern Thailand - Duangkamol Tangviriyapaiboon; Samai Sirithongthaworn; Vallop Thaineua; Siripon Kanshana; Athithan Sriminipun; Suchitporn Lersilp; Kewalin Panyo; Kansinee Changsom; Mallika Panyaphab; Pimwarat Srikummoon; Salinee Thumronglaohapun; Natthanidnan Sricharoen; et al. (BMJ Open)
Introduction The management of autism spectrum disorder (ASD) involves a varied and comprehensive range of support services at various stages of an autistic individual’s life. In Thailand, parents/legal guardians of children with ASD often encounter challenges such as difficulty travelling from rural areas to access support services. The aim of the present study is to investigate the effectiveness of a computer-based intervention programme for caregivers of children with ASD called the Thai Early Intervention for Autism—Assistive Technology for Caregivers (TEI4A-ATC), designed and implemented by a multidisciplinary team.Method and analysis 160 children and their caregivers are being recruited. They will be randomised 1:1 into two treatment arms: access to TEI4A-ATC for the intervention group and standard care for the control group. Before enrolment, ASD diagnosis will be conducted using the Thai Diagnostic Autism Scale: children’s ASD scores will be determined using the Thai Autism Treatment Evaluation Checklist for evaluating communication, sociability and sensory/cognitive awareness and the Thai Early Developmental Assessment for Intervention for evaluating motor skills, social interaction, language development and problem-solving. Both assessment tools will be used again after 3 months of treatment. Similarly, the caregivers’ knowledge, attitude and practice (KAP) for ASD care will be assessed using a questionnaire at enrolment and again after treatment. Comparison of the children’s ASD scores and caregivers’ KAP responses between the treatment groups and before and after treatment will be performed based on the intention-to-treat principle.Ethics and dissemination This study was approved by the Human Research Ethics Committee for Mental Health and Psychiatry, Department of Mental Health, Ministry of Public Health (DMH.IRB.COA 037/2565). Written informed consent will be obtained from the participants prior to enrolment. The study’s findings may be disseminated through scientific publications and conference presentations. The results of the study will be shared with key stakeholders, including caregivers, psychiatrists, policymakers and the general public, via appropriate dissemination channels to aid in creating appropriate practice and policy guidelines.Trial registration number This study was registered with the Thai Clinical Trials Registry (TCTR20240320010) on 20 March 2024.